Importantand Performance Analysis Tlngkat Kepuasan Mahaslswa Program D-3 Ekonomi Terhadap Kinerja Program D-3 Ekonomi - Khusniyah Purwani (Jurnal Aplikasi Bisnis, 2017)
The research on students satisfaction towards performance of Program Diploma III Ekonomi UII uses four variables, namely curriculum, lectures, facilities, and service. The research respondent were students of Program Diploma III Ekonomi covering those of management, accounting, and banking finance. Importance and Performance Analysis (IPA) methode used to analysis research data.The reason behind the research was Program Diplonia III Ekonomi's desire and hope to assess and evaluate the performance of the program so far. It was hoped that the research findings can be used as a reference to improve the situation in the future. On the other hand, the program mve commited to place consumer's satisfaction orientations as the main goal of the program as education institution.The research finding shows that as many as 31% or 13 attributes the main priorities to get attention and improvement. These attributes consisted of computer lab facilities, lecture room facilities, lab assistants, hot spot area, punctuality of die lectures service of Program D-3 Management, facilities of subject supporting lab. (Bank Lab, Management Lab, and Accounting Lab.), service of academy administration staff, the arrangement of computer lab, service of finance administration staff, lectures ending lectured within tolerance threshold (reducing or prolonging hours too much), availability of practicum modules, and application of subjects through practicum.